An approach of sexual education from student´s families from basic and media official educational of the municipality of Armenia, Quindío, and its influence in family dynamic (Revista de Investigaciones Universidad del Quindío, 2017)
This article emerged from the qualitative research "The approach to sex education in families of students of educational institutions of basic and official media in Armenia, Quindio, and their influence on family dynamics", funded by the Vice Presidency of Research at the University of Quindio, where changes in the functions of the sexuality of children and adolescents (NNA) within family dynamics were analyzed. For information gathering interviews with the different actors of the educational institutions and students' families were made. Also inductive categories that showed that the approach to sex education in families is limited to birth control, and sexually transmitted infections (STIs) and the desire to have a partner were consolidated; also great fear was revealed on the issue of sexuality by poor training and inadequate support from family of origin. The characteristics of the household respondents were: an average age of 40 years, secondary education, with provenance mainly from the departments of Caldas, Valle del Cauca and Putumayo, living four years ago in the city, are employed and have a reconstituted and single parent family typology. Changes in family dynamics are, mostly, setting norms and rules within the household, shared or consensual, using dialogue to solve problems and family ties strengthened through shared during leisure spaces, expressions of affection and  family support.
Keywords: Family; Sexuality; Sexual Education; Family Dynamic